Early Jewish Messianism in the New Testament : Reflections in the Dim Mirror - Ruzer, Serge, (Jewish and Christian Perspectives Series ;, 2020)
In Early Jewish Messianism in the New Testament Serge Ruzer takes a new tack on the investigation of early Christian polemical strategies against the backdrop of Second Temple Judaism. Complementing traditional inquiry on the subject, Ruzer focuses on those elements of Messiah- and Christ-centered ideas that bear witness to patterns of broader circulation - namely, the Jewish messianic ideas that provided the underpinning for the identity-making moves of Jesus' early followers. The volume suggests that such attempts can be expected to reflect eschatological ideas of the Jewish ʻOtherʼ. Exploring cases where the New Testament shows itself an early witness for belief patterns found in contemporaneous or only later rabbinic sources, this volume reveals a fuller picture of Second Temple Jewish messianism.